Analysis Of Stress Distribution Connection System To Knock Down River Ferry - Edi Jadmiko; Irfan Syarif Arief; Cahyo Putro Indro Suseno (Institut Teknologi Sepuluh Nopember, 2018)
Musi river is a wide and very long river used by local citizen for the fro. Water transportation remains the choice of local citizen though other infrastructure was built. Hence today, water transportation remains best choice because it has better time compared to landline.. This research aims to get simple solution which is quite good, effective, and quick when needed, then author made Knock Down River Ferry design. Knock Down River Ferry consists of certain size pontoon. Of course this ferry have advantages in moving and assembling. This pontoon can easly assembled in few day and various river width. In this Research there is problem identification and formulation about pontoon joints design of the ferry so force can distributed evenly when receive load.. The analysis process obtained the strength of the lock with the variety conditions of the ships, the largest stress lies on the lock number 10 on the ship moving conditions with a speed of 8 knots for 31.85 MPa with safety factor 8.635 and the lowest on the lock number 1 on the floating condition with stress for 0.91 MPa